2018
DOI: 10.1111/bju.14085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of warm ischaemia time during partial nephrectomy on renal function – is it really a matter of time?

Abstract: Impact of warm ischaemia time during partial nephrectomy on renal function -is it really a matter of time?In the latest edition of the BJUI, Lee et al. [1] have revisited the question of defining the ideal limit of warm ischaemia time (WIT) and its impact on postoperative renal function in patients undergoing partial nephrectomy (PN).Partial nephrectomy has replaced radical nephrectomy as the preferred treatment for T1 renal masses. This publication challenges the theory that ischaemic nephropathy is inevitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Also in robot assisted partial nephrectomy (RAPN), tumor complexity does not affect operative time, while for LPN it does (Faiena et al 2014;Bolton and Lynch, 2018;Luk et al 2018).…”
Section: Check After Three and Six Monthsmentioning
confidence: 99%
“…Also in robot assisted partial nephrectomy (RAPN), tumor complexity does not affect operative time, while for LPN it does (Faiena et al 2014;Bolton and Lynch, 2018;Luk et al 2018).…”
Section: Check After Three and Six Monthsmentioning
confidence: 99%
“…A review of the uro-oncology database of the SFGH revealed that from 2010 to 2017, 5.1%, 1.9%, 34.7%, 48.2% and 10% of men were treated with radical prostatectomy, brachytherapy, external beam radiotherapy, hormonal therapy and active surveillance, respectively [ 13 ]. The high proportion of men being treated primarily with hormonal therapy is not surprising given the relatively high number of Trinidadian men presenting with advanced disease compared to the developed world [ 4 ].…”
Section: Treatment Of Organ Confined Prostate Cancer In Trinidad and mentioning
confidence: 99%